Management of Participation in the Management of Islamic Educational Institutions - Nurfathatul Alfina; Mirhabun Nadir Halimy; Muhammad Bisri Ihwan (EDUTEC : Journal of Education And Technology, 2024)
The development of schools requires support from the surrounding community, often referred to as participatory management in education. This strategic approach is particularly crucial for the advancement of Islamic-based schools. This research aims to: 1) describe the process of implementing participatory management in managing Pondok Pesantren Darussalam Wonosegoro, and 2) detail the internalization of participatory management through program activities at Pondok Pesantren Darussalam Wonosegoro. The study employs a qualitative method with a descriptive approach. The research instruments include an interview guide, and data collection techniques encompass observation, interviews, and documentation. Data analysis follows the Spradley model, which includes Domain analysis, Taxonomic analysis, and Componential analysis. The findings reveal that organizing involves establishing an organizational structure that incorporates community participation. The implementation phase consists of executing the management plan and daily activities of the Islamic boarding school, necessitating active community involvement in various programs and activities. The control stage involves evaluating the achievement of goals and the performance of the pesantren, with corrective actions taken as necessary. This includes evaluating programs and activities with the community through surveys, group discussions, or joint reflection sessions. The internalization program encompasses nightly activities, delegation of students, determination of educators, and the annual commemoration of Pondok Pesantren Darussalam Wonosegoro.